2018
DOI: 10.1177/0093854818763230
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Support for Procedurally Just Treatment: The Case of the Israel National Police

Abstract: The importance of police treating citizens with procedural justice is well recognized. Recently, scholars have begun exploring officers’ views and beliefs that are associated with support for procedurally fair policing, but have not relied on a consistent conceptual framework. In the present study, we propose such a framework, focusing on three core realms of the policing environment: officers’ affiliation with their supervisors, officers’ perceptions of their authority and powers, and officers’ relationship w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 97 publications
2
40
0
Order By: Relevance
“…The evidence on Self-Legitimacy shows it fosters support for a range of pro-organizational goals. Police officers expressing confidence in Self-Legitimacy are less likely to threaten citizens with the use of force, are more committed to policing ideals, tend to embrace procedural justice in police work, and do more than is minimally required of them (Bradford & Quinton, 2014; Jonathan-Zamir & Harpaz, 2018; Trinkner, Kerrison, & Goff, 2019). In prisons, Symkovych’s (2018) study in Ukraine found that a loss of Self-Legitimacy can result in hesitancy and concession of authority.…”
Section: Self-legitimacy Relationships and Rehabilitationmentioning
confidence: 99%
See 2 more Smart Citations
“…The evidence on Self-Legitimacy shows it fosters support for a range of pro-organizational goals. Police officers expressing confidence in Self-Legitimacy are less likely to threaten citizens with the use of force, are more committed to policing ideals, tend to embrace procedural justice in police work, and do more than is minimally required of them (Bradford & Quinton, 2014; Jonathan-Zamir & Harpaz, 2018; Trinkner, Kerrison, & Goff, 2019). In prisons, Symkovych’s (2018) study in Ukraine found that a loss of Self-Legitimacy can result in hesitancy and concession of authority.…”
Section: Self-legitimacy Relationships and Rehabilitationmentioning
confidence: 99%
“…Bradford and Quinton (2014) report that officers who perceived a supportive public also tended to self-report support for the rights of suspects. In Israel, Jonathan-Zamir and Harpaz (2018) reported that police officers who perceived public support for the police were more likely to express support for the fair treatment of civilians (but see Tankebe, 2019; Tankebe & Meško, 2015). In a study in Slovenian prisons, Meško and colleagues found that prison officers who expressed commitment to fair treatment individuals in custody were officers perceived positive relations with those individuals (Meško et al, 2017).…”
Section: Self-legitimacy Relationships and Rehabilitationmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, legitimacy constrains power in normatively appropriate ways. To be seen as legitimate, authority figures need to treat individuals with respect and dignity, make decisions in open, neutral and accountable ways and respect the limits of their rightful authority (Bradford et al 2014a;Jonathan-Zamir and Harpaz 2018;Murphy and Cherney 2012;Trinkner et al 2018). On this account, legitimacy forms part of a virtuous circle.…”
Section: Introductionmentioning
confidence: 99%
“…We chose to conduct our study with them because they often see “the dark side” of society in their day‐to‐day interactions with citizens, as opposed to those who supply social services, such as nurses, teachers, and social workers. Therefore, they may be less oriented toward “fair treatment” when they believe it will limit the achievement of their organizational goals, especially when they think that their accomplishments in fighting crime are more important to the public than the fairness of their processes (Jonathan‐Zamir and Harpaz ; ).…”
Section: Methodsmentioning
confidence: 99%